Are we truly guilty? Critical notes on the theory of culpability in light of neuroscience - González Maldonado, Belén Constanza (2025)
This article seeks, through the study of neuroscience, to reexamine the concept of culpability in criminal law and its current validity in light of new neuroscientific findings, especially those related to decision-making. It questions the justification for blame, reevaluating the theory of culpability alongside these new insights. The goal is to assess whether its application is truly justified, and if not, to consider that the current intervention of criminal blame lacks sufficient grounds. By studying the neural mechanisms underlying decision-making, the traditional notion of free will is challenged, opening new perspectives for rethinking the foundations of the criminal justice system, based on the understanding that criminal actions may not be the result of conscious intent.